Pengaruh Woven Angle dan Proses Penekanan terhadap Tegangan Tarik pada Natural Fiber Laminate Composite - Anam, Khairul; Purnowidodo, Anindito; Setyabudi, Sofyan Arif (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
The aim of this study is to investigate the effects of pressure and woven angle on the tensile strength of natural fiber laminate composite. Pandanus tectorius and polymethyl methacrylate (PMMA) was used as natural fiber and matrix, respectively. The epoxy adhesive joint is used to connect between natural fiber and matrix. The pressure time of 10 s,15 s, 30 s and the pressure of 20 N/mm2, 40 N/mm2, 60 N/mm2 were used in this study. In addition, the angle of the 0o / 90o and 45o / 45o woven angle is used as the initial reference for fiber orientation before pressure is applied. From the results of the study, it can be concluded that the addition of a pressure of 60 N / mm2 and pressure time of 30 s has the highest tensile strength both at the angle of 0o / 90o and 45o / 45o. However, the tensile strength at the angle of 0o / 90o is higher that 45o / 45o. In addition, the number of adhesives decreased with increasing the pressure which will lead to delaminating.